Platform Mediation of a Self-Organized Food Network: Korgen.ax and Boundary Negotiation in REKO Åland - Preisler,Jacob Alan Sevde (2026)
The following thesis engages critically with the incorporation of a parallel digital platform alongside REKO Åland, a self-organized alternative food network operating primarily through Facebook, and how such addition of digital infrastructure reconfigures the network’s organizational boundaries. REKO’s grassroot coordination is constituted through direct producer–consumer exchange of local food, though its dependence on Facebook as the primary intermediary — which supports such functioning — imposes practical and social constraints on its operability, such as visibility concerns, administrative burden, and logistical efficiency. Through the introduction of Korgen.ax, a locally developed and embedded platform designed explicitly to address limitations of the Facebook model, the study investigates how multiple digital infrastructures mediate the balance between efficiency, self-organization, and reconnective capacity. Through employing an abductive, qualitative embedded single-case design and theory-informed thematic analysis, this thesis sources from semi-structured interviews, supplementary questionnaire responses, and analysis of Facebook posts and comment sections to demonstrate how Korgen is perceived as improving producers’ control over ordering, inventory management, and sales coordination, whilst enhancing user privacy, logistical efficiency, flexibility of direct exchange, and access beyond Facebook-based ordering altogether. Facebook, however, remains central to visibility, social interaction, and community identity. In both of these intermediaries, conditional risks persist, such as normalization or “disconnecting” tendencies. Even so, the coexistence of Facebook and Korgen produces an emerging multi-platform configuration in which social, administrative, and governing functions are distributed across infrastructures in ways that participants actively negotiate. Within its analysis, the thesis argues that Korgen reshapes REKO’s organizational boundaries, thereby revealing an additional digital boundary of self-organization. This novel boundary captures how platform choice itself becomes a form of boundary work, as participants negotiate which infrastructures legitimately organize participation, coordination, and control. From this reconfiguration, the study identifies no visible disruption to REKO Åland’s reconnective practices, particularly aspects where Korgen augments rather than replaces existing social and material relations. The study suggests the longer-term implications of multi-platform AFN configurations depend upon aspects of scale, continued participant involvement, and the ability of digital infrastructures to remain responsive to the grassroots networks they support.
Keywords: Alternative food networks; short food supply chains; REKO; Åland; self-organization; digital infrastructure; virtual reconnection; boundary negotiation; digital boundary; platform mediation; platform choice